Use of Spirulina platensis in treatment of fish farming wastewater - Nogueira, Sara Monaliza; Souza Junior, José; Maia, Hudson; Saboya, Jefferson Pablo; Farias, Wladimir (Revista Ciência Agronômica, 2018)
Each year, the amount of fish produced around the world increases, which contributes to several environmental impacts such as the disposal of effluents without treatment in the environment. This scientific work had as main objective the development of Spirulina platensis in fish effluents, a low cost medium for the production of biomass, in order to reduce the levels of some inorganic nutrients to reach the allowed parameters by the Brazilian environmental standards for effluent disposal and to enable reuse of the water. Nile tilapia (Oreochromis niloticus) fingerlings were produced in fresh water. The effluent generated by the culture was transferred to a pool where seawater was added until the salinity of 10 ‰ was reached. A strain of cyanobacteria, Spirulina platensis, was inserted into the mixture in order to remove the nutrients dissolved on the fish culture effluent. The abiotic parameters analyzed were: absorbance, pH, dissolved oxygen, temperature, salinity and concentrations of ammonia, nitrite, nitrate and phosphate. The results revealed that the maximum cellular density of S. platensis resulted in the production of 0.22 g L-1 of dry biomass and maximum productivity of 0.03 g L-1 day-1. The concentration of ammonia, nitrite, nitrate and phosphate got lowered by more than 94.8%, maintaining the nutrient levels within the standards those required by Brazilian environmental standards. Hence, this effluent has become adequate for reuse in fish production or could be safely disposed in nature.